Parallel texts from public agencies - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts from different Swedish organisations, most of them public agencies

Parallella texter från olika svenska organisationer, de flesta myndigheter
Parallella texter från myndigheter
Keywords: public administration; offentlig förvaltning; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur; Public Administration Studies; Studier av offentlig förvaltning